An improved closed loop hybrid phase shift controller for dual active bridge converter - S. Narasimha; Surender Reddy Salkuti (International Journal of Electrical and Computer Engineering (IJECE), 2020)
In this paper, a new closed loop hybrid phase shift control is proposed for dual active bridge (DAB) converter with variable input voltage. The extended phase shift (EPS) control is applied when load gets heavy enough and the secondary side phase shift angle decreases to zero. When this modified DAB converter operates at light loads, the triple phase shift (TPS) modulation method is applied, and the added control freedom is the secondary phase shift angle between the two-secondary side switching legs. The hybrid phase shift control (HPS) scheme is a combination of EPS and TPS modulations, and it provides a very simple closed form implementation for the primary and secondary side phase shift angles. Depending on the application by changing the phase shift angles we can achieve Buck or Boost operation. A characteristic table feedback control method has been used for closed loop operation. By using 1D look up table the proposed DAB converter provides constant 400V for any given input voltage.